2019
DOI: 10.3892/ijmm.2019.4089
|View full text |Cite
|
Sign up to set email alerts
|

Beclin1 inhibition enhances paclitaxel‑mediated cytotoxicity in breast cancer in�vitro and in�vivo

Abstract: Beclin1, a key regulator of autophagy, has been demonstrated to be associated with cancer cell resistance to chemotherapy. Paclitaxel is a conventional chemotherapeutic drug used in the clinical treatment of breast cancer. However, the function and mechanism of Beclin1 in paclitaxel-mediated cytotoxicity in breast cancer are not well defined. The present study demonstrated that paclitaxel suppressed cell viability and Beclin1 expression levels in BT-474 breast cancer cells in a dose-and time-dependent fashion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 53 publications
(71 reference statements)
4
10
0
Order By: Relevance
“…For instance, the suppression of Beclin1 increased TAM sensitivity in ER-positive breast cancer cells in vitro, and lower Beclin1 expression was associated with favorable outcome in patients with ER-positive breast cancer [172]. Similarly, Beclin1 inhibition enhanced paclitaxel-mediated cytotoxicity in BT-474 ER+ breast cancer cells in vitro and contributed to decreased tumor volume in a xenograft model [171], suggesting that Beclin1 protects these cells from drug-induced apoptosis. However, it is not excluded that this effect is caused by autophagy-independent functions of Beclin1.…”
Section: Autophagy Inhibitionmentioning
confidence: 96%
See 1 more Smart Citation
“…For instance, the suppression of Beclin1 increased TAM sensitivity in ER-positive breast cancer cells in vitro, and lower Beclin1 expression was associated with favorable outcome in patients with ER-positive breast cancer [172]. Similarly, Beclin1 inhibition enhanced paclitaxel-mediated cytotoxicity in BT-474 ER+ breast cancer cells in vitro and contributed to decreased tumor volume in a xenograft model [171], suggesting that Beclin1 protects these cells from drug-induced apoptosis. However, it is not excluded that this effect is caused by autophagy-independent functions of Beclin1.…”
Section: Autophagy Inhibitionmentioning
confidence: 96%
“…HER2 is known to inhibit autophagy by binding to Beclin1 [61], and HER2 amplification in breast cancer is often associated with BECN1 DNA copy loss [170]. Subsequent studies showed that Beclin1 exerts either a cytoprotective or cytotoxic effect depending on the molecular subtype [171]. For instance, the suppression of Beclin1 increased TAM sensitivity in ER-positive breast cancer cells in vitro, and lower Beclin1 expression was associated with favorable outcome in patients with ER-positive breast cancer [172].…”
Section: Autophagy Inhibitionmentioning
confidence: 99%
“…Furthermore, gene silencing of BECN-1 enhanced the efficiency of fasudil (a RhoA/ROCK inhibitor) to induce apoptosis in esophageal squamous cell carcinoma cells ( 46 ). Similarly, in vitro suppression of BECN1 reduces paclitaxel-mediated cell viability, colony formation, and induced apoptotic death in BT-474 and MDA-MB-231 breast cancer cells in dose- and time-dependent manners ( 47 ). Similar effects were observed in non-small cancer lung cancer (NSCLC) cells, endometrial carcinoma, nasopharyngeal carcinoma cells, and ovarian and renal cancers ( 48 53 ).…”
Section: Impact Of Inhibiting the Initiation And Nucleation Steps On mentioning
confidence: 99%
“…Similar effects were observed in non-small cancer lung cancer (NSCLC) cells, endometrial carcinoma, nasopharyngeal carcinoma cells, and ovarian and renal cancers ( 48 53 ). Interestingly, the therapeutic benefit of paclitaxel was increased in a Becn1 -targeted BT-474 xenograft mice model based on cleaved caspase-3 positive cells and inhibition of tumor growth ( 47 ).…”
Section: Impact Of Inhibiting the Initiation And Nucleation Steps On mentioning
confidence: 99%
“…BECN1, an essential autophagy gene, was reported to play a pivotal role in tumor biology. For example, the knockdown of BECN1 significantly enhanced breast cancer cell sensitivity to paclitaxel through caspase-dependent apoptosis [ 44 ]. Consistently, BECN1 has been reported as an oncogene in non-small-cell lung cancer, which could enhance paclitaxel resistance through involvement in autophagy in lung cancer cells [ 45 ].…”
Section: Discussionmentioning
confidence: 99%